Assessing Strategies for Heart Failure with Preserved Ejection Fraction at the Outpatient Clinic - Jorge,Antonio José Lagoeiro (2014)
Background: Heart failure with preserved ejection fraction (HFPEF) is the most common form of heart failure (HF), its diagnosis being a challenge to the outpatient clinic practice. Objective: To describe and compare two strategies derived from algorithms of the European Society of Cardiology Diastology Guidelines for the diagnosis of HFPEF. Methods: Cross-sectional study with 166 consecutive ambulatory patients (67.9±11.7 years; 72% of women). The strategies to confirm HFPEF were established according to the European Society of Cardiology Diastology Guidelines criteria. In strategy 1 (S1), tissue Doppler echocardiography (TDE) and electrocardiography (ECG) were used; in strategy 2 (S2), B-type natriuretic peptide (BNP) measurement was included. Results: In S1, patients were divided into groups based on the E/E'ratio as follows: GI, E/E'> 15 (n = 16; 9%); GII, E/E'8 to 15 (n = 79; 48%); and GIII, E/E'< 8 (n = 71; 43%). HFPEF was confirmed in GI and excluded in GIII. In GII, TDE [left atrial volume index (LAVI) ≥ 40 mL/m2; left ventricular mass index LVMI) > 122 for women and > 149 g/m2 for men] and ECG (atrial fibrillation) parameters were assessed, confirming HFPEF in 33 more patients, adding up to 49 (29%). In S2, patients were divided into three groups based on BNP levels. GI (BNP > 200 pg/mL) consisted of 12 patients, HFPEF being confirmed in all of them. GII (BNP ranging from 100 to 200 pg/mL) consisted of 20 patients with LAVI > 29 mL/m2, or LVMI ≥ 96 g/m2 for women or ≥ 116 g/m2 for men, or E/E'≥ 8 or atrial fibrillation on ECG, and the diagnosis of HFPEF was confirmed in 15. GIII (BNP < 100 pg/mL) consisted of 134 patients, 26 of whom had the diagnosis of HFPEF confirmed when GII parameters were used. Measuring BNP levels in S2 identified 4 more patients (8%) with HFPEF as compared with those identified in S1. Conclusion: The association of BNP measurement and TDE data is better than the isolated use of those parameters. BNP can be useful in identifying patients whose diagnosis of HF had been previously excluded based only on TDE findings.